Step
*
2
1
1
of Lemma
derivative-log-contraction
1. ∀a:{a:ℝ| r0 < a} . d(log-contraction(a;x))/dx = λx.r1 - ((r(4) * a) * e^x/a + e^x^2) on (-∞, ∞)
2. a : {a:ℝ| r0 < a} 
3. d(log-contraction(a;x))/dx = λx.r1 - ((r(4) * a) * e^x/a + e^x^2) on (-∞, ∞)
4. ∀x:ℝ. (r0 < (a + e^x))
5. ∀x:ℝ. (r0 < a + e^x^2)
6. x : {x:ℝ| x ∈ (-∞, ∞)} 
⊢ (r1 - ((r(4) * a) * e^x/a + e^x^2)) = (a - e^x/a + e^x)^2
BY
{ (RWO  "rnexp2" 0 THENA (Auto THEN (OrRight THENM BLemma `rmul-is-positive`) THEN Auto)) }
1
1. ∀a:{a:ℝ| r0 < a} . d(log-contraction(a;x))/dx = λx.r1 - ((r(4) * a) * e^x/a + e^x^2) on (-∞, ∞)
2. a : {a:ℝ| r0 < a} 
3. d(log-contraction(a;x))/dx = λx.r1 - ((r(4) * a) * e^x/a + e^x^2) on (-∞, ∞)
4. ∀x:ℝ. (r0 < (a + e^x))
5. ∀x:ℝ. (r0 < a + e^x^2)
6. x : {x:ℝ| x ∈ (-∞, ∞)} 
⊢ (r1 - ((r(4) * a) * e^x/(a + e^x) * (a + e^x))) = ((a - e^x/a + e^x) * (a - e^x/a + e^x))
Latex:
Latex:
1.  \mforall{}a:\{a:\mBbbR{}|  r0  <  a\}  .  d(log-contraction(a;x))/dx  =  \mlambda{}x.r1  -  ((r(4)  *  a)  *  e\^{}x/a  +  e\^{}x\^{}2)  on  (-\minfty{},  \minfty{})
2.  a  :  \{a:\mBbbR{}|  r0  <  a\} 
3.  d(log-contraction(a;x))/dx  =  \mlambda{}x.r1  -  ((r(4)  *  a)  *  e\^{}x/a  +  e\^{}x\^{}2)  on  (-\minfty{},  \minfty{})
4.  \mforall{}x:\mBbbR{}.  (r0  <  (a  +  e\^{}x))
5.  \mforall{}x:\mBbbR{}.  (r0  <  a  +  e\^{}x\^{}2)
6.  x  :  \{x:\mBbbR{}|  x  \mmember{}  (-\minfty{},  \minfty{})\} 
\mvdash{}  (r1  -  ((r(4)  *  a)  *  e\^{}x/a  +  e\^{}x\^{}2))  =  (a  -  e\^{}x/a  +  e\^{}x)\^{}2
By
Latex:
(RWO    "rnexp2"  0  THENA  (Auto  THEN  (OrRight  THENM  BLemma  `rmul-is-positive`)  THEN  Auto))
Home
Index